(untitled) - Gallicchio, Marc S. (New York, 1988)
This is a study of the Truman administration's efforts to create and implement a policy for East Asia amid the turmoil created by the collapse of the Japanese empire.
Keywords: East asia,United states,United states; Foreign relations,Foreign relations,Foreign relations; 1945-1953; United states,East asia